Development of sustainable biomaterials composites from waste materials (spent mushroom compost, garlic shell, and water hyacinth) with edible mushroom mycelium-based - Mettaya Kitiwan; Narumon Tangthirasunun; Phacharaphon Tunthawiroon (SHILAP Revista de lepidopterología, 2025)
Purpose: To evaluate performance and add value of bio-based degradable waste materials of spent mushroom compost cooperate with garlic shell, and water hyacinth with mushroom mycelium-based methods. Method: The Ganoderma lucidum, Lentinus polychrous, L. squarrosulus, and Pleurotus sajor-caju were used to study bio-based composites from various formula of waste materials (spent mushroom compost (Agrocybe cylindracea or P. ostreatus), garlic shell, and water hyacinth). Then we selected the best species and the formula of biomaterial composites to prepare pot prototypes. Finally, the biomaterial composite pots were measured physical and mechanical properties. Results: L. squarrosulus exhibited the fastest mycelial growth and highly effective to composed materials. Then, selected further pot prototypes with variation formulation and physical and mechanical properties were presented; density ranged from 0.18−0.22 g cm-3 and water absorption reaching between 172−250% in 24 hr., the absorption increases more gradually, reaching 302%−368% after 168 hr. Variations between formulation, the composites AC-F1 and PO-F1 exhibited superior water absorption. Whereas composites AC-F2 and PO-F2 demonstrated the lowest water absorption. For the compressive strength significant differences between samples prepared with spent mushroom compost from A. cylindracea and P. ostreatus. The spent mushroom compost from P. ostreatus is higher compressive strength, ranging from 385.4−451.5 kPa. In contrast the spent mushroom compost derived from A. cylindracea ranged between 174.9−197.3 kPa. Conclusion: The mycelium-based biodegradable composite produced demonstrates excellent performance and suitability for various applications. As such, they contribute to efficient upcycling and support zero-waste practices.
Keywords: Plant and Biological Electrophysiology Studies; Fungal Biology and Applications; Slime Mold and Myxomycetes Research